Pemeriksaan Lopografi Pediatric dengan Klinis Fistula Rectrovagina Post Colonostomy di Instalasi Radiologi RSUP Dr. Sardjto - Stefanie Nihe; Ari Anggraen; Ayu Mahanani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
One part of the large intestine can be affected by an anal fistula or rectovaginal fistula due to infection of the anal glands. In patients who have undergone colonostomy, radiological examinations such as lopography are necessary to detect abnormalities, especially in the anal region. Pediatric lopography with clinical rectovaginal fistula post colonostomy at the Radiology Department of Dr. Sardjito General Hospital involves inserting contrast media into the proximal section through the proximal stoma with an anteroposterior projection and into the distal section through the anal opening with a lateral projection. The study aimed to determine the contrast enema examination procedure in pediatric patients with clinical rectovaginal fistula post-colonostomy, including examination techniques, patient preparation, equipment and materials used, as well as handling problems such as blockages in the distal intestine. Methods: The study was conducted in May–June 2025 using a qualitative descriptive method through observation, interviews, and documentation, involving three radiographers and one radiologist. Data analysis was performed through data collection, data reduction, data presentation, discussion, and conclusion drawing. Results: The results showed that lopography examinations used water-soluble iodine contrast media mixed with NaCl at a ratio of 1:3, which was inserted through the proximal stoma and anus. Preparation included fasting from breast milk, confirming patient identity, informedconsent, and preparation of equipment such as an X-ray machine with fluoroscopy, catheters, syringes, and Computed Radiography.